Responsive electrolytes that inhibit electrochemical energy conversion at elevated temperatures. Issue 7 (21st February 2015) - Kelly, Jesse C.; Gupta, Rishi; Roberts, Mark E.
<x xml:space="preserve">Abstract</x> Ionic liquid-doped polymers are used as responsive electrolytes to inhibit device operation at the elevated temperatures where thermal hazards exist.